Animal sources of human campylobacteriosis : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Veterinary Public Health at Massey University, Palmerston North, New Zealand - Ahmed, Fasiuddin; Ahmed, Fasiuddin (Massey University, 1999)
New Zealand has one of the highest reported rates of Campylobacter infections in humans in the developed world. It is the single largest notifiable disease in all regions of the country. Consumption of poultry meat has been widely implicated both overseas and in New Zealand as the main cause of human infections. The potential contribution of other animals especially cattle and sheep is less well known. The present study was undertaken to fill this gap in knowledge. Faecal samples from 300 cattle and 158 sheep were collected from local abattoirs and farms plus 50 samples from the sheep slaughterhouse environment and examined for the presence of thermophilic Campylobacter spp. Campylobacter spp. were isolated from 45% of the cattle, 44% of the sheep and 56% of the environmental samples. C. jejuni and C. hyointestinalis were the predominating species isolated from cattle followed by C. coli and C. lari. In sheep and in environmental samples from the sheep abattoir C. jejuni was the only species isolated. The isolation rate and the species of Campylobacter varied between beef and dairy cattle, bull and heifer calves, age of the heifer calves, and time of the year. The high isolation rate of Campylobacter from the cattle, sheep and their environment strongly suggests the possibility of these micro-organisms finding their way into milk and meat, as faecal contaminants at the farm and slaughter level. There is also the potential to contaminate the environment and water following disposal of abattoir effluents and run off from farms The species of the isolates from human diarrhoeal cases were found to be predominantly C. jejuni (95%) and C. coli (5%). Molecular typing of C. jejuni using Sma I generated pulsed-field gel electrophoresis (PFGE) profiles yielded 13 to 16 different patterns in the cattle, sheep and human isolates showing a large inter-species variation in the isolates even from the same sources. However, indistinguishable as well as closely related profiles (pulsotypes) were found across the isolates from cattle, sheep and humans. The results obtained from the PFGE typing strongly indicate that cattle and sheep may be important reservoirs of human campylobacter infections. It was also observed that a few closely related types mostly dominate the C. jejuni populations in the host animal species. The possibility of faecal contamination from these animals at slaughter and thus C. jejuni entering the meat was studied. Retail packs of beef (25), lamb (25) and chicken (50) mince purchased from local supermarkets were examined. A combined selective enrichment and PCR based method was evaluated to offer a rapid, sensitive and specific detection method for the identification of C. jejuni from meats. C. jejuni was detected by culture and PCR in 44% of the chicken, 16% of the lamb and 12% of the beef mince samples. These results lend credibility to our contention that faecal contamination of sheep and beef carcasses at slaughter has significant implications for food safety. The much higher rate of detection in chicken mince may be related to a higher prevalence of infection in chickens or to the method of processing which may facilitate spread between birds and / or between product. The C. jejuni isolates from the animal and human sources were also examined for antibiotic resistance by the disc diffusion method to antibiotics commonly used for the treatment of campylobacter infections in humans. No resistance was detected in the cattle and sheep isolates. Two human isolates exhibited resistance to tetracycline with MICs of>128 μg/ml. All other human isolates were found susceptible to the antibiotics tested. The nil to negligible resistance detected in the animal and human isolates of C. jejuni suggest that it is not a major problem in New Zealand at the present time however, further work is required to examine the situation in more intensively farmed species and monitor any changes in human isolates over time.
Irregular pagination: missing pp78-79, but content appears complete.
Keywords: Campylobacter jejuni; Zoonoses; Cattle diseases; Sheep diseases